Front Cover: Clinical characteristics and survival of 5283 esophageal cancer patients: A multicenter study from eighteen hospitals across six regions in China. Issue 10 (19th October 2020) - He, Yutong; Liang, Di; Du, Lingbin; Guo, Tiantian; Liu, Yanyu; Sun, Xibin; Wang, Ning; Zhang, Min; Wei, Kuangrong; Shan, Baoen; Chen, Wanqing
Abstract : The cover image is based on the Original Article Clinical characteristics and survival of 5283 esophageal cancer patients: a multicenter study from eighteen hospitals across six regions in China by Yutong He et al., https://doi.org/10.1002/cac2.12087 .